Global CO2 impacts of light-duty electric vehicles. (October 2020) - Ghandi, Abbas; Paltsev, Sergey
Highlights: Methodology for modeling LDV deployment in economy-wide models is offered. Global LDV stock is projected to grow to 1.65–1.75 billion by 2050. Global electric vehicle stock is projected to grow to 585–825 million by 2050. CO2 emissions from LDV are reduced by about 50% in 2050 relative to 2015. Global carbon intensity of LDVs is reduced by about 70% from 2015 to 2050. Abstract: Electric vehicles (EV) offer a solution for decarbonization of transport. We evaluate global scenarios of EV deployment and their impacts on total global CO2 emissions. For this assessment, we enhance the MIT Economic Projection and Policy Analysis (EPPA) model to represent the fleet dynamics of light-duty vehicles (LDV), including internal combustion engine (ICE) vehicles and EVs. For EV fleet, both plug-in hybrid vehicles (PHEV) and battery electric vehicles (BEV) are considered. We consider several illustrative scenarios and find that global LDV stock is projected to grow from 1.1 billion vehicles in 2015 to 1.65–1.75 billion in 2050, while global EV stock is growing from about a million in 2015 to about 585–825 million in 2050. At this level of market penetration, EVs would constitute one-third to one-half of the overall LDV fleet by 2050 in different scenarios, with the stricter carbon constraints implied in the Paris to 2 °C scenario leading to the largest EV share. Our modeling suggests that EV uptake will vary across regions. China, the U.S., and Europe remain the largest markets in our study timeframe, but the EV presence is projected to grow in all regions. While the global LDV fleet grows by about 50% by 2050, the corresponding CO2 emissions from LDV are reduced by about 50% in 2050 relative to 2015. Global carbon intensity of LDVs are reduced by about 70% from 2015 to 2050.